Antimony and bismuth cooperation to enhance the broad yellow photoluminescence of zero-dimensional hybrid halide. Issue 26 (24th June 2022) - Cao, Jindong; Lin, Jiawei; Liu, Kunjie; Xiong, Yan; Wang, Na; He, Shihui; Zhang, Xusheng; Guo, Zhongnan; Chen, Xin; Zhao, Jing; Liu, Quanlin
Abstract : The incorporation of Sb 3+ greatly enhanced the photoluminescence quantum yield of (TMEDA)3 Bi2 Cl12 ·H2 O from 1% to 38%, the yellow emission originates from the relatively distant highly distorted inorganic octahedra in the structure. Abstract : As an emerging material, organic–inorganic metal halides (OIMHs) have been widely studied in the field of optoelectronics in recent years. In this work, a series of compounds (TMEDA)3 (Sb x Bi1− x )2 Cl12 ·H2 O (0.1 ≤ x ≤ 0.6) (TMEDA = N, N, N ′-trimethylethylenediamine) were synthesized. The incorporation of Sb 3+ greatly enhanced the photoluminescence quantum yield of (TMEDA)3 Bi2 Cl12 ·H2 O from 1% to 38%. The variation in the degree of distortion of the inorganic octahedra and the relatively suitable distances between metal ions are considered to be the reasons for the intense emission. (TMEDA)3 (Sb x Bi1− x )2 Cl12 ·H2 O (0.1 ≤ x ≤ 0.6) exhibited a yellow phosphorescence emission at 605 nm and 595 nm under excitation at 305 nm and 375 nm, respectively. With the incorporation of Sb 3+, changes in the emission intensity under different excitation wavelengths showed different trends. Thus, we attribute the yellow broadband emissions to the triplet emission of Bi 3+ and Sb 3+ . Finally, we combined (TMEDA)3 (Sb0.5 Bi0.5 )2 Cl12 ·H2 O with commercial phosphors and a near-ultraviolet light-emitting diode chip to prepare a white-light-emitting diode device, which exhibited a high color-rendering index of 94.4. The aim of our work was to investigate the structural effects of the photoluminescence of Sb 3+ -doped OIMHs and to further explore ways to improve the Sb 3+ emission efficiency in the field of photoluminescence of OIMHs.